Primary care physicians' satisfaction after health care reform: a cross-sectional study from two cities in Central Java, Indonesia - Chatila Maharani; Desie Frihandini Afief; Dorothea Weber; Michael Marx; Svetla Loukanova (BMC, 2019)
Abstract Background In 2014, Indonesia launched a mandatory national health insurance system called Jaminan Kesehatan Nasional (JKN). The reform introduced new conditions for primary care physicians (PCPs) that could influence their job satisfaction. This study assessed PCPs' satisfaction and its predictors in two cities in Central Java, Indonesia, following the reform. Methods In this exploratory, cross-sectional study, we recruited 276 PCPs from the selected area. The data were all collected in 2016 using self-report questionnaires and interviews. PCPs' satisfaction was measured using a modified version of the Warr-Cook-Wall Job Satisfaction Scale which contains 19 items and uses a Likert-type response scale. Analysis of variance, the Kruskal-Wallis H test, both with Bonferroni corrections for post hoc testing, and Cochran-Mantel-Haenszel tests were used to compare overall job satisfaction between participant groups. We used simple and multiple linear regression analyses to identify the predictors of PCP satisfaction. Furthermore, a logistic regression analysis for binary outcome was applied to model the PCPs intention to leave practice. Results PCPs' mean overall satisfaction level was 3.19 out of 5. They tended to be very satisfied with their relationship with colleagues, working hours, and physical working conditions. However, the PCPs were dissatisfied with the new referral system, the JKN health services standards, and JKN policy. The factors significantly associated with job satisfaction (p <  0.001) included type of practice, performance of managerial tasks, and PCPs' perceptions of and experiences with patients. PCP satisfaction was negatively associated (p = 0.004) with PCPs' intention to leave their practice. Conclusions The PCPs investigated in these two cities in Central Java had moderate satisfaction after the Indonesian health care reform. PCPs who worked in solo practices, performed managerial tasks, and had good experiences with patients tended to have higher satisfaction scores, which in turn prevented them from developing an intention to leave their practice. The three aspects that PCPs with which most dissatisfied were related with the JKN reform. Because of that, the government and BPJS for Health should aim to improve the JKN system in order to increase PCPs' satisfaction.